2007
DOI: 10.1017/s0014479707004942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Population Density and Sowing Date of Pumpkin on Soil Hydrothermal Regime, Weed Control and Crop Growth in a Yam–pumpkin Intercrop

Abstract: Pumpkin (Cucurbita maxima) is used for live mulch and edible apical shoots, seeds and fruits, and requires that a strategy for using it as ground cover in intercropping with food crops be developed while sustaining reasonable apical and fruit yields. Field experiments were conducted in 1999–2001 to investigate the effects of population density (5000, 10 000 and 15 000 plants ha−1) and sowing date (March, April and May) of pumpkin on the soil hydrothermal regime, earthworm casts, weed control, and crop growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Conditions of the 2002 cropping season were more favourable for soyabean and sunflower production because they were wetter and cooler than in 2001. Although changes in microclimate due to intercropping were not investigated in this study, Olasantan (2007) and Olasantan et al (2007) revealed that substantial variations in soil moisture, light interception, and air, canopy and soil temperatures under intercropping were favourably modified to benefit the growth of component crops. However, lack of appreciable yield reduction of Record and Isaanka in the mixtures suggests that these varieties have some level of compatibility with soyabean, especially TGx 1440-1E and TGx 1448-2E, compared with var.…”
Section: Discussionmentioning
confidence: 90%
“…Conditions of the 2002 cropping season were more favourable for soyabean and sunflower production because they were wetter and cooler than in 2001. Although changes in microclimate due to intercropping were not investigated in this study, Olasantan (2007) and Olasantan et al (2007) revealed that substantial variations in soil moisture, light interception, and air, canopy and soil temperatures under intercropping were favourably modified to benefit the growth of component crops. However, lack of appreciable yield reduction of Record and Isaanka in the mixtures suggests that these varieties have some level of compatibility with soyabean, especially TGx 1440-1E and TGx 1448-2E, compared with var.…”
Section: Discussionmentioning
confidence: 90%
“…The selection of variety is among the factors that contributes to the realization of a successful cropping [1][2] [9]. Hence, the fact that the total rainfall (1177.2 and 1201.6mm for 2007 and 2008 experimental years respectively) recorded at the study site fell within the range of optimum annual rainfall (1000-1500mm) reported for yam growth is not enough criteria for suitable crop variety selection in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The A horizon of the soil is an Oxic Paleudulf of the Iwo series with 83% sand, 5% silt and 12 % clay with a pH of 6 considered tolerable by yam cultivation [9]. …”
Section: Description Of Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The study area is characterized by a tropical climate with distinct wet and dry seasons with bimodal rainfall pattern and mean annual air temperature of about 30 o C. The soil at the experimental site was categorized as a well-drained tropical ferruginous soil. The A horizon of the soil is an Oxic Paleudulf of the Iwo series with 83% sand, 5% silt and 12 % clay with a pH of 6 considered tolerable by yam (Olasantan, 2007). …”
Section: Methodsmentioning
confidence: 99%